Resistance of small enterpreneurship in Croatia tourism to global health crisis - Ivan Čapeta (UTMS Journal of Economics, 2023)
Purpose - This paper focuses on the resilience of small entrepreneurship in the tourism sector of the Republic of Croatia during the global health crisis caused by the Covid-19 pandemic. Small and medium-sized enterprises (SMEs) are more vulnerable compared to larger businesses but are also more flexible and adaptable to changes in their environment. The response of SMEs to the health crisis involves innovating tourism products, expanding into other market segments, diversifying their operations, and more. Methodology - This study utilizes quantitative analysis of tourism revenue and the business performance of small and medium-sized enterprises to investigate the resilience of Croatian tourism and small entrepreneurship within the Croatian tourism industry. The results are compared with other Mediterranean countries that are members of the European Union. The study provides evidence that small entrepreneurship is more resilient to disasters caused by health crises. Findings - The research findings indicate that Croatian tourism demonstrated a faster recovery compared to other Mediterranean countries. It was also proven that small entrepreneurship is more resilient to disasters such as the health crisis caused by the Covid-19 pandemic in comparison to large enterprises.
Keywords: L83; 330; Covid-19 pandemic; business diversification; tourist flows; economic resilience